PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR KELURAHAN AIR PUTIH KECAMATAN SAMARINDA ULU - Eva Juniati (ADMINISTRASI PUBLIK, 2018)
Eva juniati, thesis entitled The Effect of Motivation on Employee Work Productivity at the Office of Air Putih Village Samarinda Ulu Subdistrict. This study aims to analize the influence of driving forces, motivation has a responsible influence, goals, desires, d significant to employee work productivity, as well as to know and describe factors that have a dominant influence on employee work productivity at the Office of Air Putih Village Samarinda Ulu Subdistrict. Data analysis techniques using product moment correlation (Pearson) or simple regression analysis, data analysis calculations using the SPSS version 23.0 for Windows program application. The population in this study amounted to 26 people. Because the population is not too large, the writer does not take a sample but the entire population is made as a respondent by cencusmethod. Based on the results of SPSS version 23.0 data analysis, the results showed that there was a positive and significant relationship between Motivation and Work Productivity variables at the Air Putih Village Office Samarinda Ulu Subdistrict. This can be seen from the results of statistical tests where the correlation coefficient r is equal to 0,858 which means there is a strong relationship between the two variables between the Motivation variables and the Work Productivity variable. This means that there is a positive influence between Motivation variables and Employee Work Productivity in the Office of Air Putih Village Samarinda Ulu Subdistrict. While the t-test (t-thets) shows that the resulting t-empirical is -8,191 this result when compared with the table of student’s critical prices for n-2 is 1,711. It turns out to be bigger, which is t count 8,191> t tab 1,711. This means that there is a significant positive effect of Motivation on Work Productivity variables. Based on the results of the Standardized Coefficients Beta the menu shows that the highest Coefficients are motivation variables which are 0,858. These results indicate that the motivation variable is a variable that influences the work productivity of employees at the Office of Air Putih Subdistrict Samarinda Ulu Subdistrict. Thus it can also be said that the formulation of the problem in this study has been answered and the proposed hypothesis can be proven to be true from the Motivation variable on Employee Productivity variables at the Office of Air Putih Village Samarinda Ulu District.